A methodological approach to organizational evaluationofinpatient, medical social and pharmaceutical care institutions that assist seniors (on the example of the Moscow boarding house for labor veterans) (Bangladesh Journal of Medical Science, 2021)
Objective: This study aims to develop methodological bases of medical social and pharmaceutical care for elderly with systemic diseases in inpatient institutions.Materials and methods: The study was done by using system, comparative, logical and retrospective analyses, as well as through content analysis and with the help of the survey method. Based on the research findings, a methodological approach was developed.Results and Discussion: This study examined the organizational structure and living environment of the Moscow boarding house for labor veterans and determined the distribution of diagnoses in the population of boarding house residents. The paper also provides information on gender and age differences in cardiovascular morbidity among older adults.Conclusion: The paper presents patient satisfaction ratings with the quality of medical, social and pharmaceutical services provided in the examined boarding house against 6 criteria. The satisfaction survey results suggested high quality of care delivery.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.809-816